Influence of COVID-19 on Mental Health of Young Families Residing at Harion Municipality in Sarlahi District of Nepal - Thapaliya, Samjhana; Giri, Surendra (Journal of Health Promotion, 2023)
Since the WHO declared COVID-19 as a pandemic, the spread of the COVID-19 was the focus of attention of scientists, governments and populations. One of the main concerns was the influence of this pandemic on people’s health, mainly on mental health. This study is an in-depth analysis of the influence of COVID-19 and its measurement policies on mental health of young families residing at Harion municipality in Sarlahi district of Nepal. Husserl phenomenology approach was used to explore the experience of young families. Four participants were phone interviewed using a semi-structured interview schedule to elicit their experiences of COVID-19 and its influence on their mental health. The analysis was carried out under three major themes: (1) ‘COVID-19 and its influence’, (2) ‘Lockdown and its effects’, and (3) ‘COVID-19 and strategies for the prevention from this disease’. Fear of getting disease and being affected themselves and their beloved ones and end of life was one of the main causes. Another cause by the lockdown created financial challenges and loneliness with serious mental health problem in young families. The findings highlight the influences of COVID-19 and its measurement policies effects in mental health and different ways of coping strategies adopted by young families in Nepal.